Enhancing the efficiency of infrared drying of desiccated coconut through process optimization and validation - Sahari, Yahya; Anuar, Mohd Shamsul; Mohd Nor, Mohd Zuhair; Abdul Ghani, Nur Hamizah (Universiti Putra Malaysia Press, 2025)
Drying desiccated coconut is always challenging due to its sensitivity to heat, which can reduce its color quality. The main goal of this study is to optimize infrared drying (IR) efficiency without affecting the final color quality of desiccated coconut. Single-mode infrared drying was optimized using Response Surface Methodology (RSM) with a central composite rotatable design (CCRD). Using a radiation output of 600 Watts and a fixed distance of 15 cm from the emitter, a single layer of fresh shredded coconut with a wet basis of approximately 51.35±4.0% was dried to less than 3% (w.b). Drying temperature and air velocity were taken into consideration as independent parameters. The selected optimal drying conditions, with the desirability value (D = 0.812), were 61°C drying temperature and 2.2 m/s air velocity. The response of optimal values for drying time, specific energy consumption (SEC), color changes, and whiteness index were 36.826 minutes, 19.821 kWh/ kg, 3.431, and 71.762, respectively. Models for predicting these response values had R2 values of more than 0.90. All responses were shown to be significantly impacted by drying temperature and air velocity (p<0.05), with drying temperature having a larger effect than air velocity. The optimal drying parameters were validated with a less than 2% deviation.